Odpowiedzi

2010-03-27T20:17:28+01:00
A1,a2,a3,a4, .... - nieskończony ciąg geometryczny, taki że
a1 = -1
oraz a3 - 2a4 = 8a2 + 4
mamy
a2 = a1*q = - q
a3 = a1 *q² = - q²
a4 = a1 *q³ = = - q³
czyli
-q² + 2q³ =- 8*q + 4
2q³ - q² + 8q - 4 = 0
2q*(q² +4) -(q² +4) = 0
(2q - 1)*( q² + 4) = 0 , ponieważ q² +4 > 0
zatem
(2q -1)*(q² +4) = 0 <=> 2q = 1 <=> q = 1/2
a) q = 1/2 = 0,5
b)
Ponieważ
a1 = -1 <0 oraz q = 1/2 > 0 , to ciąg an = -(1/2)^(n-1) jest rosnący.
Mamy
-1,-1/2,-1/4/,-1/8,-1/16, - 1/32,-1/64,-1/128,-1/256, ...


3 5 3